2022
DOI: 10.1038/s41598-022-08484-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning approach for chemistry and processing history prediction from materials microstructure

Abstract: Finding the chemical composition and processing history from a microstructure morphology for heterogeneous materials is desired in many applications. While the simulation methods based on physical concepts such as the phase-field method can predict the spatio-temporal evolution of the materials’ microstructure, they are not efficient techniques for predicting processing and chemistry if a specific morphology is desired. In this study, we propose a framework based on a deep learning approach that enables us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 79 publications
(82 reference statements)
0
2
1
Order By: Relevance
“…However, it has to be remarked that the GBT does not include the material history in its prediction, which is contradicting plasticity theory on a first glance [55]. In literature, LSTMs are frequently employed for data series predictions since it has been found that they are able to take into account the influence of preceding microstructure evolution [27,28,56]. This is not explicitly found in our study since the GBT shows better results compared to the LSTM.…”
Section: Discussioncontrasting
confidence: 68%
“…However, it has to be remarked that the GBT does not include the material history in its prediction, which is contradicting plasticity theory on a first glance [55]. In literature, LSTMs are frequently employed for data series predictions since it has been found that they are able to take into account the influence of preceding microstructure evolution [27,28,56]. This is not explicitly found in our study since the GBT shows better results compared to the LSTM.…”
Section: Discussioncontrasting
confidence: 68%
“…[35] To get high prediction accuracy we also use transfer learning method. [36] For our dataset, we obtained 7000 fluorescent microscopy images (Figure S14) to confirm whether dependences between Mg 2+ concentration and the structures of assembled capsules and their fluorescence intensities existed. We formed the reaction-diffusion systems containing 0 mM, 10 mM, 50 mM, 200 mM, or 500 mM Mg 2+ .…”
Section: Prediction Of Mg 2+ Concentration From Fluorescent Images By...mentioning
confidence: 96%
“…Meanwhile, in order to overcome the limitation of PCA as a 1D dimensionality reduction method, some studies have utilized tensor decomposition [135,136] instead of PCA or employed autoencoders as a nonlinear feature extraction method. [137][138][139][140] Moreover, more complex and effective models for the prediction of spatiotemporal sequences, such as ConvLSTM, [137][138][139] E3D-LSTM, [141] and PredRNN, [142] have also been applied to predict long-term microstructures with heightened efficiency and precision. In addition, for systems with overdamped kinetics, such as defect kinetics in lamellar morphology, some studies have successfully employed acceleration schemes without time dependence, like FFT+CNN, [143] which predict the microstructure at time t + Δt based on that at time t. Since this task is similar to traditional deep learning tasks, such as video prediction, [144] future research might develop more advanced prediction algorithms for enhancing the speed and accuracy of predictions.…”
Section: Accelerating Simulationsmentioning
confidence: 99%